The Impact of Anesthesia Type During Cesarean Section on Maternal and Neonatal Outcomes at Fakeeh Hospital - Batayah, Eman A. (Journal of King Abdulaziz University: Medical Sciences, 2023)
The World Health Organization has highlighted the importance of improving maternal and neonatal health. Their health could be affected by the anesthesia type given during cesarean section. The study aim is to assess the effect of spinal and general anesthesia on maternal and neonatal outcomes during elective cesarean section. Quantitative observational study was conducted at Fakeeh hospital in Jeddah, Saudi Arabia. 295 participants were included to spinal anesthesia group (n = 285) and general anesthesia (n = 10). A purposeful sampling was used to invite the study participants and structured questionnaire was developed to assess the impact of anesthesia type during cesarean section. The study results provide evidence that spinal anesthesia is more practiced in healthcare settings compared to general anesthesia. The results also showed an effect of general anesthesia on maternal outcomes in which mothers had more intra-operative blood loss, tachycardia, request for analgesia in a short period and neonatal outcomes as low first minute Apgar scores, low skin to skin contact, and low breast-feeding rates. In conclusion, spinal anesthesia was the method of choice in elective cesarean section due to its benefits for both mother and newborn.